2018
DOI: 10.33373/jtp.v2i2.1469
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Pelaksanaan Rencana Pembangunan Jangka Menengah Daerah (Rpjmd) Bidang Urusan Pekerjaan Umum Kabupaten Kepulauan Anambas, Provinsi Kepulauan Riau

Abstract: Tulisan ini berisi hasil penelitian mengenai pembangunan daerah sebagai bagian intergral dari pembangunan Nasional dilaksanakan berdasarkan prinsip otonomi daerah dan pengaturan sumber daya Nasional untuk meningkatkan kesejahteraan masyarakat di Provinsi Kepulauan Riau khususnya di Kabupaten Kepulauan Anambas. Rencana Pembangunan Jangka Menengah Daerah adalah Rencana pembangunan daerah berdurasi 5 tahun yang didalamnya terdapat penjabaran visi misi pemerintahan daerah. RPJMD Kabupaten Kepulauan Anambas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is also confirmed by findings (Wahyuddin, 2017) regarding implementing the Education and Health Sector of Berau Regency in 2010-2015. The weak bureau cratic capacity will hinder the success of RPMJD programs, such as in the gap between the Plan and Implementation of the Pasuruan Regional Medium-Term Development Plan (RPJMD) 2013-2018 (Widiyanti, 2019), the Public Works Affairs Sector Program ofthe Anambas Islands Regency (Lestari, Rini, & Dwiyanti, 2018). From the perspective of participation, (Yandra, 2016) found that in the preparation of the Pekanbaru City RPJMD, this participation had not effective because the community was not involved from the start in the RPJMD Formulation so that the community was stillseen as a subject in development.…”
Section: Panasmentioning
confidence: 99%
“…It is also confirmed by findings (Wahyuddin, 2017) regarding implementing the Education and Health Sector of Berau Regency in 2010-2015. The weak bureau cratic capacity will hinder the success of RPMJD programs, such as in the gap between the Plan and Implementation of the Pasuruan Regional Medium-Term Development Plan (RPJMD) 2013-2018 (Widiyanti, 2019), the Public Works Affairs Sector Program ofthe Anambas Islands Regency (Lestari, Rini, & Dwiyanti, 2018). From the perspective of participation, (Yandra, 2016) found that in the preparation of the Pekanbaru City RPJMD, this participation had not effective because the community was not involved from the start in the RPJMD Formulation so that the community was stillseen as a subject in development.…”
Section: Panasmentioning
confidence: 99%
“…The fishery potential of the Kepulauan Anambas District is inversely proportional to the achievements in the performance of fisheries affairs for the 2016-2020 period. According to RPJMD data, the amount of capture and aquaculture production is unstable and tends to decrease every year, while the available facilities or fleets tend to increase (Lestari et al, 2018). Few facts explain that the increasing number of fishermen is not directly proportional to the amount of production produced, so this raises the assumption that the number of fish in the waters of Anambas is decreasing.…”
Section: Introductionmentioning
confidence: 99%